Communication Strategy on Environmental Law for Waste Management in Bukittinggi City - Anggi Putri Kurniadi; Susi Evanita (Universitas Widya Gama Malang, 2020)
This study aims to inform and persuade the community of Bukittinggi City in Mandiangin Koto Selayan Subdistrict to apply the environmental law Bukittinggi City Regulation No. 5 of 2014 concerning waste management and levies / cleaning services because there is a point of waste accumulation in Mandiangin Koto Selayan Subdistrict, even though Bukittinggi received the Adipura award in the last three years in a row. The action to anticipate this problem is through a communication strategy on environmental law for waste management in Bukittinggi City to maintain a clean environment by using a hierarchy effect model. The results showed that waste management was not optimal due to the low awareness of the community in disposing of waste according to Bukittinggi City Regulation Number 5 of 2014. Based on this, waste management was not neatly arranged which had an impact on environmental degradation and aesthetic disturbances. The study recommends that communication of environmental law and implementation of waste management need to be improved so that Bukittinggi City can maintain the Adipura award in the future.